Magnetic outflows from turbulent accretion disks: I. Vertical structure and secular evolution - Jacquemin-Ide, J.; Lesur, G.; Ferreira, J. (Astronomy and astrophysics (Berlin), 2021)
Context. Astrophysical disks are likely embedded in an ambient vertical magnetic field generated by its environment. This ambient field is known to drive magneto-rotational turbulence in the disk bulk, but it is also responsible for launching magnetised outflows at the origin of astrophysical jets. Yet, the interplay between turbulence and outflows is not understood. In particular, the vertical structure and long-term (secular) evolution of such a system lack quantitative predictions. It is, nevertheless, this secular evolution which is proposed to explain time variability in many accreting systems such as FuOr, X-ray binaries, and novae like systems. Aims. We seek to constraint the structure and long-term evolution of turbulent astrophysical disks subject to magnetised outflows in the non-relativistic regime. More specifically we aim to characterise the mechanism driving accretion, the dynamics of the disk atmosphere, the role played by the outflow, and the long-term evolution of mass and magnetic flux distributions. Methods. We computed and analysed global 3D ideal magnetohydrynamic (MHD) simulations of an accretion disk threaded by a large-scale magnetic field. We measured the turbulent state of the system by Reynolds averaging the ideal MHD equations and evaluate the role of the turbulent terms in the equilibrium of the system. We then computed the transport of mass, angular momentum, and magnetic fields in the disk to characterise its secular evolution. Finally, we performed a parameter exploration survey in order to characterise how the transport properties depend on the disk properties. Results. We find that weakly magnetised disks drive jets that carry a small fraction of the disk angular momentum away. The mass-weighted accretion speed remains subsonic, although there is always an upper turbulent atmospheric region where transsonic accretion takes place. We show that this turbulence is driven by a strongly magnetised version of the magneto-rotational instability. The internal disk structure therefore appears drastically different from the conventional hydrostatic picture. We expect that the turbulent atmosphere region will lead to non-thermal features in the emission spectra from compact objects. In addition, we show that the disk is subject to a secular viscous-type instability, which leads to the formation of long-lived ring-like structures in the disk surface density distribution. This instability is likely connected to the magnetic field transport. Finally, we show that for all of the parameters explored, the ambient magnetic field is always dragged inward in the disk at a velocity which increases with the disk magnetisation. Beyond a threshold on the latter, the disk undergoes a profound radial readjustment. It leads to the formation of an inner accretion-ejection region with a supersonic mass-weighted accretion speed and where the magnetic field distribution becomes steady and reaches a magnitude near equipartition with the thermal pressure. This inner structure shares many properties with the jet emitting disk model. Overall, these results pave the way for quantitative self-consistent secular disk models.